Association between the developing sphenoid and adult morphology: A study using sagittal sections of the skull base from human embryos and fetuses. Issue 6 (15th July 2021) - Yamamoto, Masahito; Jin, Zhe‐Wu; Hayashi, Shogo; Rodríguez‐Vázquez, José Francisco; Murakami, Gen; Abe, Shinichi
Abstract: The developing sphenoid is regarded as a median cartilage mass (basisphenoid [BS]) with three cartilaginous processes (orbitosphenoid [OS], ala temporalis [AT], and alar process [AP]). The relationships of this initial configuration with the adult morphology are difficult to determine because of extensive membranous ossification along the cartilaginous elements. The purpose of this study was therefore to evaluate the anatomical connections between each element of the fetal sphenoid and adult morphology. Sagittal sections from 25 embryos and fetuses of gestational age 6–34 weeks and crown‐rump length 12–295 mm were therefore examined and compared with horizontal and frontal sections from the other 25 late‐term fetuses (217–340 mm). The OS was identified as a set of three mutually attached cartilage bars in early fetuses. At all stages, the OS‐post was continuous with the anterolateral part of the BS. The BS included the notochord and Rathke's pouch remnant in embryos and early fetuses. The dorsum sellae was absent from embryos, but it protruded from the BS in early fetuses before a fossa for the hypophysis became evident. Although not higher than the hypophysis at midterm, the dorsum sellae elongated superiorly after gestational age 25 weeks. In early fetuses, the AP was located on the side immediately anterior to the otic capsule. The AT developed on the side immediately posterior to the extraocular rectus muscles. At late term, the greater wing was formed by membranous bones from the AT and AP. The AT and AP formed a complex bridge between the BS and the greater wing. A small cartilage, future medial pterygoid process (PTmed) was located inferior to the AT in early fetuses. At midterm, one endochondral bone and multiple membranous bones formed the PTmed. The lateral pterygoid process (PTlat) was formed by a single membranous bone plate. Therefore, we connected fetal elements and the adult morphology as follows. (1) Derivative of the OS makes not only the lesser wing but also the anterior margin of the body of the sphenoid. (2) Derivatives of the BS are the body of the sphenoid including the sella turcica and the dorsum sellae. (3) Most of the greater wing including the foramen rotundum and the foramen oval originate from the AT and AP and multiple membranous bones. (4) The PTmed originate from endochondral bones and multiple membranous bones, while the PTlat derive from a single membranous bone. Abstract : The ala temporalis (AT) was found to surround the maxillary nerve and to face the Vidian nerve. The prenatal life, the alar process connected the basisphenoid (BS) to the AT‐derived greater wing. Alongside the BS, paramedian parts of the late‐term sphenoid was much thinner than the adult morphology.